An Investigation of Internal Factors Affecting the Motivation of Turkish EFL Learners in a Negative Way - Funda Güç; Devrim Höl (Literacy Trek, 2018)
This paper aims to find out the factors affecting the L2 motivation of Turkish EFL learners in a negative way and discover whether gender, type of education and the level of the students have an impact on their motivation. The data gathered from 205 prep-class students at Pamukkale University School of Foreign Languages showed that although there were no differences in the factors in terms of learners' type of education and the level of English, an important and meaningful difference between male and female learners was found. Based on the findings, the implications of the results and suggestions for future research are discussed.